Difference in Psychosocial Well-being Between Paternal and Maternal AIDS Orphans in Rural China - Zhao, Qun (2010)
This study compares psychosocial well-being between paternal and maternal orphans in rural China in a sample (N = 459) of children who had lost one parent to HIV and who were in family-based care. Measures included academic marks, education expectation, trusting relationships with current caregivers, self-reported health status, depression, loneliness, posttraumatic stress, and social support. No significant differences were found between maternal and paternal orphans, except that paternal orphans reported better trusting relationships with caregivers than maternal orphans. Children with a healthy surviving parent reported significantly better depression, loneliness, posttraumatic stress, and social support scores than children with a sick parent. Analyses revealed significance with regard to orphan status on academic marks and trusting relationships with caregivers while controlling for age, gender, surviving parent’s health status, and family SES. Findings underscore the importance of psychosocial support for children whose surviving parent is living with HIV or another illness.